MOTOR ACTIVITY OF CHILDREN DURING STAY IN A PRESCHOOL EDUCATIONAL INSTITUTION - Sosunovsky, V.S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the volume of motor activity of preschool children during their stay in a preschool educational institution. Methods and structure of the study. To collect information on the number of motor acts of preschool children during the study, the method of shagometry was used. The number of locomotions was counted using a Yamax DW-200 Sh 25 pedometer manufactured by Yamasa Corp., Tokyo, Japan. The scientific research was carried out during the cold period of the year from November to March. A total of 234 children were tested. Results and conclusions. With the help of shagometry, differences in motor activity were revealed between boys and girls 3-4 years old and 5-6 years old during their free motor activity. It has been determined that the organization of motor activity during a walk is an important form of a child’s physical activity, since it includes the largest number of locomotions performed by the child during the day. Therefore, it is necessary to develop programs for the physical education of preschool children, which will be aimed at the effective implementation of their motor activity during a walk, as well as the creation of a developing object-spatial environment for the territory of a walk for preschoolers using sports simulators and equipment.